Analyzing the Spread of Informal Employment in Russia: Reasons, Forms and Spheres of Concentration - M. I. Glinskaya (Вестник Российского экономического университета имени Г. В. Плеханова)
One important problem of economy at the current stage of society development is the increase in proportion of informally employed population in the total amount of labour. The prolonged trend of this indicator growth requires serious attention to this problem. Topicality of this problem is stipulated by increasing disturbance in society arising due to the growth in the number of informally employed population, non-observance of labour legislation standards and therefore, employees’ uncertainty about tomorrow. The author analyzes reasons for informal employment, identifies key spheres of its concentration and forming the full picture of problem non-uniformity. The basis of the research is formed by methods of analysis and synthesis of statistic data, which is published annually on the official portal of the Federal service of state statistics. Findings of the research shown in the article demonstrate characteristic features typical of informal employment in today’s society and analyze reasons and sphere of concentration of informally employed population. The obtained conclusions can be used as substantiation for the concept of regulating informally employed people on the territory of the Russian Federation.